THE ROLE OF IMMUNOSTIMULANTS IN THE PREVENTION OF COLIBACILLOSIS IN CALVES - Navruzov N. I. (International Engineering Journal For Research & Development, 2020)
When a vaccine is used wint xitozan (a natural clear solution) then the immune globulin in calf’s organ become permanent.